Congenital hiatal hernia segregating with a duplication in 9q22.31q22.32 in two families. Issue 12 (7th October 2020) - Chang, Caitlin A.; Di Donato, Nataliya; Hackmann, Karl; Argiropoulos, Bob; Ferreira, Patrick; Innes, A. Micheil; Thomas, Mary Ann
Abstract: Congenital hiatal hernia (HH) is a rare congenital defect and is often described on a sporadic basis, but familial cases have also been reported. The mechanism of development is not well understood, and to our knowledge no specific genetic factors have been implicated to date. We report on seven individuals from two families with 9q22 duplication, who have variably associated features including congenital HH in four individuals. One family had an 1.09 Mb 9q22 duplication, and the other family had an overlapping 2.73 Mb 9q22 duplication. We review the genes in this region and discuss BARX1 (BarH‐like homeobox gene 1) as a gene of interest.